Management Lessons from the Battle of Uhud - Omar, Azura (IIUM Journal of Case Studies in Management, 2025)
The Battle of Uhud is the second great battle between the Quraish of Mecca against the Muslims of Medina. Regarded as one of most important battle in Islamic history by many Muslim scholars, the Battled of Uhud was Quaraish’s revenge over their defeat at Badr. Like in the Battle of Badr, the Muslims were outnumbered and relied on war strategies carfted by the Prohpet (pbuh). The Muslims won the initial scrimmage but lost the battle.